ANALYSIS OF STANDARD TIME IN INCREASING PRODUCTION CAPACITY AT PT SPG USING SHUMARD ADJUSTMENT METHOD (International Journal of Psychosocial Rehabilitation, 2020)
Production is an activity undertaken to create new products or goods that can add value to a product in order to increase its usefulness. Products or goods that are produced are usually different for each company and for each period, according to what the company is engaged in, and one company can produce various kinds of goods or products. PT SPG is a company engaged in the field of food production and distribution of snacks, especially fish crackers. Consumer demand for products in this company compels them to try to meet consumer needs, so that almost every day the company produces and stores stock of products in case of a sudden purchase. Stockpile often occurs due to overproduction. Maximum production capacity per day is 1500 packs. The problem is to be solved by finding the standard time of production using the Shumard method. This study was conducted using the data derived from every part of the production. The expectation of this study was to determine the standard time of production in order to meet consumer needs and avoid heap of stockpile in storage. The results from the research concluded that the measurement of cycle time, normal time and standard time for the production of crackers, are respectively 48.58 seconds for cycle time, 56.82 seconds for normal time and 67.96 seconds for standard time, and 4.5 seconds for standard time, in the calculation of company’s productivity. The application of cycle, normal, and standard time in the production process has different implications such as the amount of product output, psychological and physiological factors of the operators, fatigue, production costs and the quality of the products produced. The total output of cracker products that can be produced by PT SPG based on Time calculation is 2800 packs of products.